Pengaruh Media Pendingin Terhadap Kekerasan Baja Tahan Karat Martensitik Type 431 Pada Proses Hardening dan Tempering - Suyanta Suyanta; Subagiyo Subagiyo; Syamsul Hadi; Zahratul Jannah (Polinema Press, Politeknik Negeri Malang, 2018)
Stainless steels consist of several types such as Austenitic, Ferritic and Martensitic, Martensitic is one of the stainless steels that has a hardenability property, so it is suitable to be used as cutting tool components which require high hardness and corrosion resistance . The purpose of this study was to obtain information about the hardness of stainless steel martensitic type of hardening results with variations of cooling media. Methods of research used were experiments, ie hardening process by heating the material up to 1100oC temperature, held for 30 minutes, then cooled quickly on water, oil and the air, then heated back to 400oC temperature, cooled slowly, the results tested the hardness of Rockwell C method The results showed the type of stainless steel type martensitic 431 increased significantly after the Hardening process of 21.20 HRC before hardening, and after the hardening process to 47 , 6 HRC with water cooling, 47.9 HRC with oil cooling medium and 46.5 HRC for air cooling media, hardness after tempering down ranges from 6-7 HRC to 41.7 HRC for hardening with water cooling medium 41, 2HRC hardening results with oil cooling medium, and 40,4HRC un tuk hardening results with air conditioning medium.